Unidentified street in Beacon Hill, ca. 1950 - Neiley, Robert (Tufts Archival Research Center, 2005)
Street-level view of an unidentified street in Beacon Hill. An automobile is parked on a side road just off the main street. 9 12 x 7 9/16, 9 15/16 x 8 overall Photographs